Optimization of Production Inputs and Business Scale in Whiteleg Shrimp (Penaeus vannamei) Cultivation in Bantan District, Bengkalis Regency, Riau Province (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
This study analyzes the factors influencing whiteleg shrimp (Penaeus vannamei) production and the efficiency of input utilization in pond farming in Bantan District, Bengkalis Regency, Riau Province. Data was collected from 40 farmers through a census approach. Data was analyzed through multiple linear regression based on the Cobb–Douglas production function, supplemented by classical assumption tests, allocative efficiency measurements, and return to scale analysis. The results indicate that key production factors include pond area, stocking density, feed quantity, pond age, and water quality. Among these, feed quantity was found to be significant (p < 0.05) and the dominant factor, with an elasticity coefficient of 0.990. The coefficient of determination (R²= of 0.989) indicates that the model explains 98.9% of the variation in production. Elasticity and allocative efficiency analyses reveal that input utilization has not yet reached optimal levels, while the estimated scale (1.118) indicates an increasing return to scale (IRS) condition. The economic implications of these findings emphasize the importance of efficient feed management to enhance productivity and income, while other factors remain relevant in supporting business sustainability. These results provide important insights for policymakers and local stakeholders to promote efficient resource allocation, strengthen farmer capacity, and develop sustainable shrimp farming strategies that improve coastal community welfare.